Comparison of Pethidine and Tramadol for the Control of Shivering in Patients undergoing Elective Surgery under Spinal Anesthesia - Sharma, Mahesh; Kharbuja, Kalpana; Khadka, Bikash (Journal of Lumbini Medical College, 2017)
Introduction: Shivering is a common problem faced by an anesthesiologist during intraoperative as well as in postoperative period. It is a frequent, unpleasant, and undesirable complication occurring after sub-arachnoid block (SAB), secondary to vasodilation as a result of sympathetic blockade. The incidence of shivering has been reported to be about 36-85% after SAB. The present study was designed to compare the efficacy of pethidine and tramadol on reducing postoperative shivering following sub-arachnoid block and to compare their adverse effects.Methods: This randomized, experimental study was conducted in patients undergoing surgery under sub-arachnoid block over a four months period. Patients were randomized into Group P (receiving pethidine) or Group T (receiving tramadol). Patients received either tramadol or pethidine in a dose of 0.5mg/kg intravenously after the appearance of shivering. Disappearance of shivering as well as hemodynamics were observed at scheduled intervals.Result: Shivering score was significantly lower in Group P at 10, 15, 20, and 30 min compared to Group T. Similarly, nausea/vomiting and dizziness were also lower in Group P but sedation score was higher.Conclusion: Pethidine provide better antishivering effect than tramadol with less side effect in terms of nausea and vomiting but more sedation.J. Lumbini. Med. Coll. Vol 4, No 2, July-Dec 2016, page: 66-67DOI: https://doi.org/10.22502/jlmc.v4i2.92